EPIDEMIOLOGICAL ANALYSIS OF TUBERCULOSIS BY AGE GENDER, AND TYPE OF TUBERCULOSIS IN DISTRICT KARAK, KHYBER PAKHTUNKHWA, PAKISTAN (The Research of Medical Science Review, 2024)
Background: Tuberculosis (TB) is a major public health concern both globally and in Pakistan. Understanding the epidemiology of tuberculosis, particularly its distribution by age, gender, and type, is critical for effective control and preventative efforts. Objective: This study seeks to examine the epidemiological patterns of tuberculosis by age, gender, and type in District Karak, with a particular emphasis on data from 2022 and 2023Methods: A retrospective investigation of 6,182 TB patients reported at DHQ Hospital Karak was carried out. The data were divided into three categories: gender, year of registration, and kind of tuberculosis (pulmonary vs. extra-pulmonary). Throughout the study period, the age-specific prevalence of smear-positive patients for both pulmonary and extra pulmonary tuberculosis was determined. Results: The male-female ratio was practically equal, with 51.15% males and 48.85% females. TB cases were higher in 2023 (53.70%) than in 2022 (46.30%), while infection prevalence was higher in 2022 (34% vs. 29.58%). The overall prevalence of tuberculosis was 31.62 percent. Pulmonary tuberculosis accounted for 77% of cases, much more than extra-pulmonary tuberculosis (23%). Pulmonary tuberculosis was most common in children aged 0 to 4 years (24.97% in 2022 and 15.46% in 2023). Extra-pulmonary tuberculosis showed a similar trend, with the highest frequency in the 0-4 age range (6.16% in 2022 and 7.94% in 2023). Conclusion: The findings show that pulmonary TB predominates over extra pulmonary TB in District Karak, with a considerable burden in young children. These findings highlight the importance of targeted interventions, as well as improved diagnostic and treatment procedures, for combating tuberculosis, particularly in disadvantaged populations.